Development of an Atlantic salmon (Salmo salar) genetic improvement program : genetic parameters of harvest body weight and carcass quality traits estimated with animal models - Quinton, Cheryl D.; McMillan, Ian; Glebe, Brian D. (Elsevier, 2005)
v 2005 ok